Nilai Pendidikan Karakter pada Novel Si Anak Pelangi Karya Tere Liye dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia - Putri Agustina, Ria; Khalidatun Nuzula; Haniatus Sholikhah (EduInovasi: Journal of Basic Educational Studies, 2025)
The purpose of this research is to describe the values of character education in the novel Si Anak Pelangi by Tere Liye through a pragmatic approach and its implications for Indonesian language learning. This study employs a descriptive qualitative method. The data in this research consists of dialogues between characters in the novel Si Anak Pelangi by Tere Liye. The study analyzes the manifestation of character education values using a pragmatic approach. The data collection technique used is the read-and-note technique, aimed at obtaining analysis results and an overview of the character education values present in the novel. The data analysis follows the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The character education values found in the novel Si Anak Pelangi include the 18 character education values defined by the Indonesian Ministry of Education and Culture. Based on the analysis, a total of 41 character values were identified. These include: 4 religious values, 8 honesty values, 4 tolerance values, 2 discipline values, 3 hard work values, 1 creativity value, 1 independence value, 2 democratic values, 1 curiosity value, 1 spirit of nationalism value, 2 patriotism values, 1 appreciation for achievement value, 1 friendship value, 2 love of peace values, 1 reading habit value, 1 environmental care value, 2 social care values, and 4 responsibility values. The analysis of character education values in the novel Si Anak Pelangi by Tere Liye can be implemented in Indonesian language learning, particularly in the study of novels. Novel material appears in the advanced-level Indonesian language and literature textbook for 12th grade in the Merdeka Curriculum (Phase F), under the topic “Analyzing Values in Novel Excerpts.” The Learning Outcomes (Capaian Pembelajaran - CP) applied include the reading and viewing component, where students are asked to analyze dialogues in the novel, and the speaking and presenting component, where students present their analysis of the dialogues to the class and respond to peer feedback. The implication of this research takes the form of a teaching module for analyzing values in novels and a Student Worksheet (Lembar Kerja Peserta Didik - LKPD).